Effects of thermal and non-thermal processing on quality attributes of chokanan mango juice (Mangifera Indica L.) / Vicknesha a/p Santhirasegaram - Santhirasegaram, Vicknesha (2015)

(untitled)
The increasing demand for high quality fruit juice, along with safety standards have spurred the development of non-thermal processing such as sonication and ultraviolet-c (UV-C) light treatment. In this study, freshly squeezed Chokanan mango juice was subjected to thermal treatment (at 90 °C for 30 and 60 seconds), sonication (for 15, 30 and 60 minutes at 25 °C, 40 kHz frequency) and UV-C treatment (for 15, 30 and 60 minutes at 25 °C, 254 nm). In addition, combination of sonication (for 15 and 30 minutes at 25 °C, 40 kHz frequency) and UV-C treatment (for 15 and 30 minutes at 25 °C, 254 nm) in a hurdle concept was also conducted. The effects of thermal and nonthermal treatments on various quality parameters (microbial inactivation, physicochemical properties, colour, clarity, browning index, total carotenoid and ascorbic acid content, antioxidant activities, sensory attributes) were evaluated and compared with untreated juice (control). After thermal and non-thermal treatments, no significant changes were observed in pH, total soluble solids and titratable acidity. However, significant differences in colour, browning index and ascorbic acid content of juice were observed after treatments (thermal and non-thermal). Non-thermal treatments showed significant improvement in selected quality parameters. Overall, sonication and UV-C treatment (as a stand-alone and combined treatment) exhibited significant enhancement in clarity, antioxidant activities, and extractability of carotenoids, polyphenols, and flavonoids, when compared to the control. In addition, significant reduction in microbial load was observed in non-thermal and thermal treatments. Although thermal treatment was iii effective in completely inactivating microbial growth in juice, significant quality loss was observed. The individual phenolic compounds in juice were identified and quantified using liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis. The results showed better retention of individual phenolic compounds in non-thermal treated juice, when compared to the control and thermally treated juice. Sensory attributes (colour, odour, taste, and overall acceptability) were evaluated by 90 panellists using a hedonic scale, and results showed that non-thermal treated juice was preferred more than thermally treated juice. The sensory evaluation verified that the combination of sonication and UV-C was the most acceptable treatment of the selected non-thermal treatments. The shelf life of the thermally treated juice stored at 4 °C was extended for at least five weeks longer than control. With regards to sonication and UV-C treatment (as a standalone), the shelf life of juice stored at 4 °C was extended for at least four weeks longer than control. Besides that, combined treatment prolonged the shelf life of juice stored at 4 °C for at least five weeks longer than control. The results obtained support the use of non-thermal treatments (ultrasound and UV-C) for better retention of quality along with safety standards in Chokanan mango juice processing. Combination of ultrasound and UV-C therefore, is a promising alternative to thermal treatment.